TEORI PERTUMBUHAN BERBASIS EKONOMI (EKSPOR) : POSISI DAN SUMBANGANNYA BAGI PERBENDAHARAAN ALAT-ALAT ANALISIS REGIONAL - Prasetyo Soepono (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
The determinants of regional growth are demand and supply. Demand as a factor for explaining regional growth inquires where the demand comes from and traces its impact through the regional economic system, where a demand for a regional output gives rise to other regional output by way of backward linkages. The export-based theory of growth claims demand as the determinant of regional growth. It seeks to identify the region’ s export activities, to forecast the growth in the activities, and to evaluate the impact of that additional export activity on the other or non-basic activities of the region. The export-based theory plays the role of identifying which sectors/ industries are basic and which ones are non-basic after those sectors/ industries undergoing a shift-share analysis. The export –based theory offers various techniques of determining what a basic sector industry is and various wyas of calculating economic base multipliers. The export-based theory has some disadvantages: no inter-regional inter-industry interdependence, short-run analysis, etc. However, one thing the export-based theory can contribute is that it is useful for small regions like a district (kecamatan), regency (kabupaten) in determining their ability to export and is the first to apply the macro-economic model of income determination to regions.Keywords: basic & non-basic sectors, location quotient, economic base multiplier